Front Cover: Carbon Neutralization, Volume 1, Issue 3, December 2022. Issue 3 (16th December 2022) - Lin, Congjian; Zhang, Jintao; Lim, Yew Von; Yan, Dong; Li, Ke; Leong, Zhi Yi; Vafakhah, Sareh; Li, Yifan; Silva, Arlindo; Yang, Hui Ying
Abstract : Front cover image: In article number 10.1002/cnl2.26, Hui Ying Yang and co‐workers focus on a low‐cost method to fabricate an advanced sodium anode. The leftover cooked rice is shown here as an important element. By effective multi‐step heat treatment, the anode of CoSe2 nanoparticles embedded in a matrix containing carbon nanotubes and rice‐derived hard carbon can be synthesized. The red spheres in the battery represent electrons and sodium ions. The intrinsically formed 3D network is effective in shortening the diffusion paths of both electrons and sodium ions, leading to fast transport and impressive sodium storage characteristic.